A comparative review of China, India and Pakistan renewable energy sectors and sharing opportunities. (May 2016) - Ahmed, Saeed; Mahmood, Anzar; Hasan, Ahmad; Sidhu, Guftaar Ahmad Sardar; Butt, Muhammad Fasih Uddin
Abstract: China, India and Pakistan (CIP) contain almost 40% of the world population and constitute a developing region which is desperately seeking energy resources to fulfill the growing economy requirements. CIP are three main countries of South Eastern Asia with nuclear capability and have greater potential of energy sharing for the regional prosperity and socio economic development. The total energy consumption of China and India is 3682.15 Million tons of Oil Equivalent (MTOE) which is approximately 28% of the world. The energy consumption of Pakistan is far less i.e. 85.75 MTOE however, it can play a pivotal role by providing energy sharing opportunities in the region. This paper presents a comparative and comprehensive review of CIP renewable energy sectors and possible sharing opportunities. Cleaner and abundant Renewable Energy Sources (RES) like hydro, solar, wind, biomass, nuclear and geothermal have been discussed and compared in context of CIP energy requirements. CIP relations and energy sharing opportunities have also been elaborated in context of regional peace and security situation. Exploitation of the CIP energy potential and energy sharing opportunities might contribute to global peace and prosperity.